2021
DOI: 10.1021/acsptsci.1c00224
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Receptor GPR35 Suppresses Lipid Accumulation in Hepatocytes

Abstract: Although prevalent, nonalcoholic fatty liver disease is not currently treated effectively with medicines. Initially, using wild-type and genome-edited clones of the human hepatocyte cell line HepG2, we show that activation of the orphan G protein-coupled receptor GPR35 is both able and sufficient to block liver X-receptor-mediated lipid accumulation. Studies on hepatocytes isolated from both wild-type and GPR35 knock-out mice were consistent with a similar effect of GPR35 agonists in these cells, but because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Therefore, we hypothesized that GPR35 might affect FAO by activating HIF-1α. In contrast, GPR35 might modulate the concentrations of relevant metabolites by affecting classic FAO targets, such as peroxisome proliferator-activated receptor [38], PGC-1α [19,39], and LXR [29,39]. For example, activated GPR35 up-regulates PGC-1α [19], and PGC-1α in turn increases FAO to meet energy requirements [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we hypothesized that GPR35 might affect FAO by activating HIF-1α. In contrast, GPR35 might modulate the concentrations of relevant metabolites by affecting classic FAO targets, such as peroxisome proliferator-activated receptor [38], PGC-1α [19,39], and LXR [29,39]. For example, activated GPR35 up-regulates PGC-1α [19], and PGC-1α in turn increases FAO to meet energy requirements [39].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of PEs has been implicated in many metabolic diseases, such as atherosclerosis, insulin resistance, and obesity [43,44], as well as several chronic diseases, such as Alzheimer's disease, Parkinson's disease, and nonalcoholic liver disease [44,45]. GPR35 has also been implicated in type 2 diabetes mellitus [26,28] and nonalcoholic liver disease [29], among others. Furthermore, GPR35, through up-regulation of PGC-1α, significantly affects the expression of genes associated with lipid metabolism, thermogenesis, and anti-inflammation in adipose tissue [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, emerging evidence from experimental and clinical studies has linked altered hepatic cholesterol homeostasis and FC accumulation to NASH pathogenesis 9 , 10 . Several in vitro studies have indicated that GPR35 activation inhibits lipid accumulation in hepatocytes 50 , 51 . Nevertheless, the identity of the class of toxic lipids regulated by GPR35 and the mechanism are not known.…”
Section: Discussionmentioning
confidence: 99%
“…GPR35 represents the verified target of the mast-cell-stabilizing, approved antiallergic drug lodoxoamid (6) and is involved in a variety of physiological processes. GPR35 controls lipid metabolism and stimulates thermogenic programs in adipocytes as well as immune cell recruitment in different situations (7)(8)(9) while its function in the intestine is associated with inflammatory bowel disease, bacterial infection and oncogenic signaling (10)(11)(12)(13)(14)(15). In the heart, hypoxia-inducible factor-1 (HIF-1)mediated upregulation of GPR35 expression during cardiac infarction is associated with the disruption of the actin cytoskeleton arrangement and is suggested as an early marker of progressive cardiac failure (16,17).…”
Section: Introductionmentioning
confidence: 99%